2015
DOI: 10.3109/10641955.2014.988352
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester angiotensing-converting enzyme and uterine artery Doppler as predictors of preeclampsia in a high-risk population

Abstract: ACE, PI and RI as parameters of Doppler study were useful predictors of PE in the second trimester of gestation. The best combination to increase the diagnostic performance was ACE with the RI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…When ACE is over‐expressed due to genetic factors, RAS will be overactive and the function of prostaglandin (PG) system will be disordered, resulting in vasoconstriction, which plays a certain role in the pathogenesis of pre‐eclampsia. Ruiz et al 9 . reported that serum ACE levels in pregnant women with pre‐eclampsia were significantly higher than those without pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…When ACE is over‐expressed due to genetic factors, RAS will be overactive and the function of prostaglandin (PG) system will be disordered, resulting in vasoconstriction, which plays a certain role in the pathogenesis of pre‐eclampsia. Ruiz et al 9 . reported that serum ACE levels in pregnant women with pre‐eclampsia were significantly higher than those without pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia risk factors include obesity, insulin resistance, and hyperlipidemia, which can stimulate the release of inflammatory and oxidative stress, leading to endothelial dysfunction 4 . In preeclampsia, there was abnormal invasion of trophoblast cells and destruction of the physiological remodeling of the uterine spiral artery into uterine placental vessels observed in normal pregnancy 5 , 6 . Severe preeclampsia may be associated with thrombocytopenia, multiple organ damage, and fetal growth restriction 7 .…”
Section: Introductionmentioning
confidence: 99%